SENGKETA PEMBANGUNAN PANGKALAN MILITER CHINA DI KEPULAUAN SPRATLY ANTARA CHINA DAN FILIPINA BERDASARKAN UNCLOS 1982: The Dispute over China's Construction of Military Bases in the Spratly Islands between China and the Philippines Based on UNCLOS 1982 - Averroes Gazalba Gofa; Y. Fitriliani (Faculty of Law, Universitas Trisakti, 2025)
The Spratly Islands, located in the southern region of the South China Sea (SCS), are claimed by China as part of its territorial sovereignty based on the Nine-Dash Line theory. This claim has led to disputes between China and the Philippines, Vietnam, Brunei Darussalam, and Malaysia. In its efforts to assert control over the SCS, China has unilaterally engaged in militarization by constructing military bases in the Spratly Islands. The problem issues are as follows: whether the construction of military bases by China in the Spratly Islands constitutes a violation under UNCLOS 1982; and how the dispute regarding China's military base construction in the Spratly Islands between China and the Philippines can be resolved under UNCLOS 1982. The results and conclusion indicate that China’s construction of military bases in the Spratly Islands contravenes principles of international law, including violations of the sovereign rights of coastal states within their Exclusive Economic Zones (EEZs). UNCLOS 1982 provides various dispute resolution mechanisms, such as negotiation, mediation, arbitration, and international litigation through the International Tribunal for the Law of the Sea (ITLOS).